24 Cross-talk of tumor cells with mesenchymal stromal cells enhances tumor progression in head and neck cancer. Issue 5 (May 2015) - ; Kansy, B.; Bruderek, K.; Dumitru, C.; Lang, S.; Brandau, S.
Abstract : Introduction: Mesenchymal stromal cells (MSC) are multipotent fibroblast-like progenitor cells and represent an integral cellular component of the tumor stroma. However, little is known about their role in the tumor microenvironment of head and neck squamous cell carcinoma (HNSCC). The aim of this study was to isolate and characterize MSC from HNSCC and to investigate their interaction with tumor cells. Methods: MSC were isolated from tumor tissues of HNSCC patients during routine oncological surgery. The cytokine profile of tumor-derived MSC was determined by enzyme-linked immunosorbent assay (ELISA). Activation of MSC by tumor-conditioned media was assessed by measuring cytokine release and expression of CD54. The effect of MSC on HNSCC cells in vitro was assessed by measurement of proliferative, migratory and invasive capabilities of HNSCC cells after coculture with tumor-derived MSC. Additionally the impact of MSC on tumor growth in vivo was analyzed in a HNSCC xenograft model. Results: Cells isolated from HNSCC tissue met the consensus criteria for MSC in terms of tri-lineage differentiation and immunophenotype. MSC produced high amounts of interleukin (IL)-6, IL-8 and stromal cell-derived factor (SDF)-1 α . Soluble factors secreted from HNSCC cell lines activated MSC resulting in enhanced secretion of IL-8 and induced expression of CD54. Conversely, MSC directly stimulated the proliferation, migration and invasion of HNSCC cells in vitro. In vivo, co-injection of MSC with human HNSCC cell lines strongly enhanced tumor growth in a murine xenograft model. Conclusions: MSCs were successfully isolated, characterized and expanded from malignant tissue of HNSCC patients. We observed cross-talk of MSC and HNSCC cells in vitro and in vivo resulting in reciprocal stimulation of both cells types and enhanced growth of HNSCC cells in vivo. Our results suggest an active role of the tumor stroma in tumor progression.